Tsenguluso ya U tambudzwa ha vhana zwi tshi tikedzwa nga Mafenya L.L "ndi bune-de" na Nefefe M.P. "Milomo ya nukala" - Mavhusha, Takalani Irene (My University, 2010)
The first chapter has outlined the backgmund of the problem . This was followed by the aim of the study. The methods of the study that will be used were dealt with ,and different aspects were briefly explained. Chapter two has classified and discussed some types of child abuse, abusers and the abused, causes and effects of child abuse . I n chapter three and four the researcher con centrated on giving the analysis of child abuse as portrayed in Mafe nya LL. 'Ndi bune-<je' an d 􀁠efefe M.P. 'Milomo ya [Iuka/a' respectively. The last chapter is the concluding chapter whereby through the fi ndings, the society and authors of Tshivemja drama books may re alise the seriousness of child abuse an d its negative impact to the community. As a result, authors may realise the need to have more dr ama books that will concentrate on this theme, thus con tributing towards the protection of South African children against exploitation that they are facing in their daily lives
Thesis ( M.A. (African Languages)) -- University of Limpopo, 2010
Keywords: Child abuse; Abusers; Abused; Emotionally; Child abuse; Abused children